2009
DOI: 10.1038/msb.2009.2
|View full text |Cite
|
Sign up to set email alerts
|

Glucose regulates transcription in yeast through a network of signaling pathways

Abstract: Addition of glucose to yeast cells increases their growth rate and results in a massive restructuring of their transcriptional output. We have used microarray analysis in conjunction with conditional mutations to obtain a systems view of the signaling network responsible for glucose-induced transcriptional changes. We found that several well-studied signaling pathways-such as Snf1 and Rgt-are responsible for specialized but limited responses to glucose. However, 90% of the glucoseinduced changes can be recapit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
221
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(237 citation statements)
references
References 47 publications
10
221
1
Order By: Relevance
“…This is consistent with the recent report that PKA is not involved in the degradation of Mth1 (29). Previous genome-wide expression analysis has established PKA as the predominant glucose signaling kinase that is responsible for nearly 90% of the transcriptional changes in response to glucose (30). It has been reported to phosphorylate Rgt1, leading to the inhibition of its chromatin-binding activity (1,29).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the recent report that PKA is not involved in the degradation of Mth1 (29). Previous genome-wide expression analysis has established PKA as the predominant glucose signaling kinase that is responsible for nearly 90% of the transcriptional changes in response to glucose (30). It has been reported to phosphorylate Rgt1, leading to the inhibition of its chromatin-binding activity (1,29).…”
Section: Discussionsupporting
confidence: 92%
“…Expression of the TCA cycle and OXPHOS genes is regulated by glucose levels independently of PKA and SNF1 by the Hap2/3/4/5p transcription complex, suggesting that the Hap2/3/4/5p complex provides an additional mechanism of transcriptional regulation of mitochondrial respiration (5). The Hap2/3/4/5p complex binds to DNA through the Hap2, -3, and -5 subunits, which are constitutively expressed.…”
Section: Resultsmentioning
confidence: 99%
“…The preferred sources of carbon and energy for the yeast Saccharomyces cerevisiae are fermentable sugars such as glucose (3)(4)(5). When yeast cells are grown in liquid cultures in rich media containing glucose under aerobic conditions, the cells metabolize glucose predominantly by glycolysis, producing pyruvate.…”
mentioning
confidence: 99%
“…The observation that glucose but not Snf1 inhibition caused a rapid dissociation of ADH2 from polysomes suggested that a glucose-dependent signaling pathway might be required for this process. cAMP-dependent protein kinase (protein kinase A [PKA]) is a major regulator of pathways active during fermentation (5,76), and low PKA activity inhibits translation during glucose starvation (73). Whether PKA plays a role in glucose-induced mRNA decay is unknown.…”
Section: Figmentioning
confidence: 99%
“…as , TPK2 as , and TPK3 as (76), were derepressed for 4 h either in the presence or in the absence of the inhibitor 2NM-PP1. Then, samples of both cultures were removed for RNA isolation and quantitation.…”
Section: Figmentioning
confidence: 99%